3 - Between Tunnel Vision and a Sliding Scale: Power, Normativity and Justice in the Praxis of the International Criminal Court - Okafor, Obiora Chinedu; Ngwaba, Uchechukwu (Africa Development, 2021)
This article examines the relatively extensive, liberal and increasing deployment of the International Criminal Court (ICC) as the central mechanism for redressing gross human rights abuses in Africa. It shines the spotlight on how global and domestic power matrices affect the character and behaviour of international criminal justice norms and institutions, including our sense of what the model approach to international criminal justice ought to be in Africa and elsewhere. Three inter-related arguments are advanced as follows: first, the deployment of the ICC to help redress gross human rights abuses on the African continent has its pros and cons, but its deployment to play a central role as it currently does is fraught with suspicion as regards the true intention; second, when it comes to redressing the gross human rights abuses that are committed on the African continent, as elsewhere, the ICC is not the only viable and available option – there are a range of other reasonable options in the repertoire of international criminal law and policy; and third, it is largely because of the interplay of domestic and global power matrices (and not in the main because of some immanent sense of morality or logic) that international criminal justice has increasingly tended to take one particular, generally inflexible, ICC-heavy, form in its encounters with gross human rights abuses in Africa.